Numerical study on hysteretic characteristics of transmission tower K-joints - Jian Zhang; Guangchen Wu; Lidong Yang (Frontiers in Materials, 2022)
Introduction: The mechanical properties of joints have a significant impact on the dynamic response of transmission tower structures.Methods: Considering bolt slip, the numerical model of the transmission tower K-joint is established. The mechanical properties of K-joints are studied from three aspects: failure mode, load-displacement hysteretic curve, and stiffness degradation by numerical method. The effects of bolt preload, friction coefficient, and member strength on the hysteretic properties of the K-joint are analyzed.Results: The results show that due to the complexity of K-joints, bolt slip will lead to the reduction of ultimate bearing capacity and the change of failure position. In order to accurately obtain the mechanical properties of K-joints, the influence of bolt slip should be considered in the research process; The plumpness of load-displacement hysteretic curve is greatly affected by parameters; The stiffness of K-joints degenerates with the increase of loading times.Discussion: The results provide a reference for the mechanical analysis of the transmission tower.